Scientific Study about Feminism in Iraqi Society - Huwail, Riyadh Mohsen; Ali, Hani Mohammed Saeed Mohammed (Journal of Innovation in Education and Social Research, 2024)
A number of resistance activities against the idea of patriarchy, social injustice, and capitalism's involvement in the oppression of women encouraged to the social movement known as feminism. Feminist theory started out as a disorganized and inconsistent system of opposition to phallocratic (2) thought and behavior, but it has developed into a reputable field of study and critical analysis. The subject of how women's autonomous identities can be asserted and formed in both the social and literary fields is within the purview of feminist literary theory, it also develops in parallel with male literary discourse. Thus, in order to define, develop, and complete social justice for women in all classes of society, we are pleased to welcome today a wide and diverse variety of feminist philosophers who employ poststructuralist, psychoanalytic, Marxist (1), and postcolonial ways to reduce the centralization of masculine ideology. The depict "pro-feminism" is most often used to describe men who actively aid feminism movement; it does not reveal that the supporter is a member of the feminist movement. Men's groups that sustain feminism engagement in anti-violence initiatives in educational and teaching foundations and with young men, providing a workshop on sexual harassment at work, calling to community education events, or going camping, and providing counseling to males who commit acts of violence against women, as well as participating in men's health activism.